Who’s Afraid of Derrida? Gumbrecht and the metaphysics of presence - de Souza, Gustavo Ramos de Souza (Revista Brasileira de Estudos da Presença, 2023)
This paper proposes a reflection on the concept of presence theorized by Hans Ulrich Gumbrecht premised on Heidegger’s thought, contrasting it with the philosophy of Jacques Derrida, especially in his deconstruction of the metaphysics of presence. Accordingly, it is neither a matter of tracing the Heideggerian presence throughout his oeuvre nor of defending Derrida from the accusations of linguistic existentialism, but rather of demonstrating that, by having Heidegger as an ally, Gumbrecht’s crusade against metaphysics and the hermeneutic field ultimately restores them more strongly, thereby he commits to what he aims to oppose.